Antiparasitic Efficacy of Herbal Extracts and Active Compound Against Gyrodactylus kobayashii in Carassius auratus - Zhou, Shun; Dong, Jing; Liu, Yongtao; Yang, Qiuhong; Xu, Ning; Yang, Yibin; Ai, Xiaohui (Frontiers in Veterinary Science, 2021)
Gyrodactylus spp. Nordmann, 1832 (Monogenea: Gyrodactylidae) are common ectoparasites of teleost fishes. Infection with these parasites can increase the mortality of fish and cause considerable economic losses in intensive aquaculture. To find an effective antiparasitic agent for the control of gyrodactylosis, antiparasitic efficacy of crude extracts of 36 herbal medicines was evaluated using a Carassius auratus (Cypriniformes, Cyprinidae) - Gyrodactylus kobayashii model. Among all tested medicines, methanol extract of Dioscorea collettii var. hypoglauca (Dioscoreales, Dioscoreaceae) was the most efficient, with an EC50 value of 4.17 mg/L. This extract showed 100% antiparasitic efficacy against G. kobayashii at 10 mg/L and had a therapeutic index (TI, LC50/EC50) of 5.26, which is higher than that of formaldehyde (TI = 4.58), a widely used parasiticide in aquaculture. Subsequently, the potential mechanism of antiparasitic activity of dioscin, an active compound isolated from D. collettii var. hypoglauca was investigated and the histopathological alterations in goldfish after exposure to dioscin were also studied. The in vivo trial indicated dioscin showed significant antiparasitic activity with a 24 h-EC50 value of 1.58 mg/L and it exhibited 100% antiparasitic efficacy at 0.6 mg/L. Also, G. kobayashii could be completely removed in vivo within two hours at 0.6 mg/L dioscin. Whereas mean survival time of this worm in vitro was 4.99 hours, and some individuals even reached 12 hours at the same concentration of dioscin. These results indicated that 0.6 mg/L of dioscin did not completely kill all worms within two hours, but just temporarily remove the worms from goldfish. Scanning electron microscopy (SEM) analysis showed that most of the microvilli on the tegument surface of G. kobayashii dropped after exposure to dioscin. This might be one of the potential mechanisms of antiparasitic activity of dioscin against G. kobayashii. Furthermore, no severe histopathological alteration was observed after exposure to a high concentration of dioscin for a short time. Considering both effectiveness and safety, therapeutic baths with a high concentration of dioscin for a short time might be a more optimal choice for the treatment of gyrodactylosis in aquaculture.